Developing and Validating the Glocal Competency Scale for Primary School Teachers to Adapt Global Standards to Indonesian Local Contexts - Annas Solihin; Neni Mariana; Suryanti Suryanti; Ganes Gunansyah; Ika Rahmawati; Yunia Tiara Riski (Pedagogy Review, 2026)
This research develops and preliminarily validates the Glocal Competency Scale for Primary School Teachers (GCS-PST), an instrument designed to measure the capacity of Indonesian primary school teachers to translate globalized curriculum standards into glocalized values within local cultural contexts. The widespread influence of global educational frameworks such as Global Citizenship Education (GCE) and Education for Sustainable Development (ESD) requires teachers to contextualize international standards within culturally specific local settings. Existing teacher competency instruments address either global or local dimensions in isolation, producing a measurement gap for the integrated glocal competency construct. To address this gap, the study employed a Research and Development (RD) paradigm across four systematic stages: (1) comprehensive literature review, (2) item development based on five theoretically grounded dimensions, (3) expert judgment using Content Validity Index (CVI) calculations, and (4) field-testing combined with in-depth qualitative exploration involving 30 primary school teachers. This study adopted an Explanatory Mixed-Methods design: quantitative descriptive data from scale responses were explained and enriched by open-ended responses, interviews, and direct observations from the same 30 participants. Content validity was evaluated using CVI calculations, while reliability was assessed using Cronbach’s alpha and McDonald’s omega. Results demonstrate acceptable preliminary psychometric properties with overall reliability coefficients of α = 0.87 and ω = 0.89. Descriptive analysis shows that participants exhibited moderate to high levels of glocal competency across all five dimensions. Qualitative findings further illuminate how teachers perceive and enact glocal competency in their daily practice. The five-dimensional structure encompasses Situated Global Practice, Glocal Curriculum Design, Critical-Cultural Awareness, Local Cultural Awareness and Expression, and Intercultural Collaboration and Digital Mediation. Keywords: Glocal competency, Primary school teachers, Instrument development, Global citizenship education, Cultural adaptation.